The Development of Academic Self-Efficacy Scale for Filipino Junior High School Students - Dullas, Angelo Reyes (Frontiers in Education, 2018)
Primarily the research is focused on the development and validation of the Academic Self-efficacy Scale (ASES-FJHS) for Filipino junior high school students. Self-efficacy refers to people’s beliefs in their capabilities to produce certain effects and to learn or perform behaviors at designated levels (Bandura, 2012; Bandura, 2006). In relation to test construction, most of the developed self-efficacy scale focuses on one source of self-efficacy and are constructed as subscale. Given the limited published academic self-efficacy scale for Filipino junior high school students as well as the non-existence of published and established academic self-efficacy scale in Philippine context, this study sought to develop and validate a self-efficacy scale that is more holistic than those previously published. The design of the research is Test Development and anchored on Classical Test Theory. Respondents comprise of 4,759 junior high school students from selected 20 public and private schools in Nueva Ecija, Philippines. The study followed the two stages of test development, i.e. the development of the initial, preliminary and final forms and validation of the scale. The items were developed through consultation with experts and literature reviews. After the development of table of specification, items were validated by four expert judges. Results showed using Lawshe CVR (CVI=.87) and Intra Class Correlation (ICC(2,4)=.953, a=.000) that the expert validators have high agreement on the items of ASES. Moreover, UL-LL method (d=.43), Cronbach alpha (.95), split half method (Spearman-Brown Coefficient=.86) and item to total correlation, and Principal Component Analysis were also utilized to test the reliability of test items. The factor structure verified the four iterations which includes Perceived Control (PC), Competence (C), Persistence (P) and Self-Regulated Learning (SRL) domains. Convergent (r = .498; p < .05) and concurrent validity (r = .518; p < .01) that were employed suggest that the ASES is a valid measure. The Final Form validated consists of 62 items. Results of the study revealed that the ASES for K to 12 junior high school students is a reliable and valid measure of Academic Self-efficacy.